2018
DOI: 10.1126/science.aaq1704
|View full text |Cite
|
Sign up to set email alerts
|

Infrared hyperbolic metasurface based on nanostructured van der Waals materials

Abstract: Correspondence to: r.hillenbrand@nanogune.eu Metasurfaces with strongly anisotropic optical properties can support deep subwavelength-scale confined electromagnetic waves (polaritons) that promise opportunities for controlling light in photonic and optoelectronic applications. We develop a mid-infrared hyperbolic metasurface by nanostructuring a thin layer of hexagonal boron nitride supporting deep subwavelength-scale phonon polaritons that propagate with in-plane hyperbolic dispersion. By applying an infrared… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
327
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 414 publications
(338 citation statements)
references
References 36 publications
5
327
0
6
Order By: Relevance
“…Many of these have been realized in hyperbolic metasurfaces, created by artificial subwavelength structuring from visible to microwave frequency ranges . However, in such artificially created hyperbolic surfaces, the wave vector of plasmon polaritons is limited by the inverse of the structure size, which hinders the potential of hyperbolic plasmons . The anisotropic 2D materials present a natural platform for realizing the planar hyperbolic plasmons with much larger momentum, which may fulfill the applications with enhanced light–matter interaction and near‐field radiative heat transfer as a result of higher electromagnetic confinement and more diverging photonic density of states.…”
Section: Plasmons In Anisotropic 2d Materialsmentioning
confidence: 99%
“…Many of these have been realized in hyperbolic metasurfaces, created by artificial subwavelength structuring from visible to microwave frequency ranges . However, in such artificially created hyperbolic surfaces, the wave vector of plasmon polaritons is limited by the inverse of the structure size, which hinders the potential of hyperbolic plasmons . The anisotropic 2D materials present a natural platform for realizing the planar hyperbolic plasmons with much larger momentum, which may fulfill the applications with enhanced light–matter interaction and near‐field radiative heat transfer as a result of higher electromagnetic confinement and more diverging photonic density of states.…”
Section: Plasmons In Anisotropic 2d Materialsmentioning
confidence: 99%
“…For that reason, these materials can support polaritons (excitations resulting from strong light–matter interactions) whose momentum k describes a hyperbolic isofrequency curve in momentum space. As a consequence, the so‐called hyperbolic polaritons (HPs) propagate highly directional and with extremely short wavelengths and strong field confinement, which makes them promising candidates for future nanophotonic applications including nanoscale focusing and guiding . HPs have been studied essentially in slabs and resonator structures .…”
mentioning
confidence: 99%
“…These HPPs were not observed with the photothermal microscope (Figure ) due to the lower signal strength of the illumination/detection technique. Interestingly, Li et al very recently demonstrated concave wavefronts of a diverging polariton beam in a h‐BN grating structure with a 100 nm pitch. Although the thicker region of the h‐BN grating in this work did have a stronger scattering amplitude, the s‐SNOM technique did not conclusively demonstrate HPPs propagating within the patterned grating region.…”
Section: Resultsmentioning
confidence: 99%